2015
DOI: 10.17795/iji-31548
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Residual Spraying Coverage and Acceptability Rates to Control Malaria and the Householders’ Reasons of Acceptance or Rejection of Spraying, in South-East of Iran

Abstract: Background: Indoor residual spraying (IRS), as one of the malaria control techniques, requires high spraying coverage and acceptance rate by householders, to be effective. Objectives:The main aim of the study was to assess the spraying acceptability and coverage rates in relation to acceptance and rejection reasons of the IRS program. Also, the householders' perception about IRS benefits and satisfaction with the malaria prevention and knowledge of transmission pathways were estimated. Materials and Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
3
14
1
Order By: Relevance
“…This study showed a high level of knowledge about malaria transmission and symptoms in the study population. Similar findings have also been reported from other malaria-endemic areas in the southeast of Iran [ 10 , 14 , 19 ]. Also, high awareness of people about malaria transmission and symptoms has been reported from other malaria-endemic countries including Malaysia, Saudi Arabia, Swaziland, Ethiopia, Ghana and Tanzania [ 17 , 20 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed a high level of knowledge about malaria transmission and symptoms in the study population. Similar findings have also been reported from other malaria-endemic areas in the southeast of Iran [ 10 , 14 , 19 ]. Also, high awareness of people about malaria transmission and symptoms has been reported from other malaria-endemic countries including Malaysia, Saudi Arabia, Swaziland, Ethiopia, Ghana and Tanzania [ 17 , 20 24 ].…”
Section: Discussionsupporting
confidence: 90%
“…National malaria control programmes in the 91 endemic countries reported that 106 million people worldwide were protected by IRS in 2015 [ 1 ]. Several factors which influence the effectiveness of IRS interventions include spraying coverage, type of insecticide, type and situation of houses, community awareness and cooperation, household acceptance, and informing the households about the programme benefits and spraying time during the spraying campaign [ 10 ]. Spraying coverage is also dependent on the household’s perception of the effectiveness of IRS programme against mosquitoes and other nuisance insects, as well as the number and intensity of unwanted side effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 62 63 The most commonly cited barriers to participation included fear of theft during control activities, 64 odours and allergic reactions to insecticide 65 and logistical challenges. 66 67 While community engagement and mobilisation activities were associated with higher rates of participation, 68–70 these strategies have not been evaluated in a randomised trial.…”
Section: Discussionmentioning
confidence: 99%
“…4 Again in a cross sectional study conducted by Sakeni et al in South East Iran revealed that IRS coverage and acceptance were 96.5% and 94%, respectively which is higher than the present study. 5 The wide variation in the coverage and acceptance was due to refusal by head of the family due to bad smell, white spot, and still biting of mosquito which points towards the lack of insecticidal effect or inappropriate spraying and the unavailability of IRS workers which is probably due to the lack of programmatic management. Similar reasons of refusal were also reported by Ronghangpi et al and Mazigo et al in their study in Assam and Rural North East Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…1 NVBDCP has suggested LQAS surveys to be carried out in high-risk district to track IRS coverage at health institution level. [2][3][4][5][6] The North-Eastern state Tripura being endemic for malaria, control measures like IRS are of utmost importance. But the acceptance has been limited over the years and there is least information on the factors responsible for it.…”
mentioning
confidence: 99%